3-D Interaction of a Corner Flaw with a Non-Aligned Surface Flaw in an Infinitely Large Plate under Tension. (2015) - Ma, Q.; Levy, C.; Perl, M.
Abstract: The evaluation of non-aligned multiple flaws is required in various Fitness-for-Service codes. For non-aligned parallel cracks, on-site inspection needs to decide whether they should be treated as coalesced or separate multiple cracks for Fitness-for-Service. Criteria and standards for the adjustment of multiple nonaligned cracks are very different from one source to another in the existing literature. And those criteria and standards are often derived from on-site service experience without rigorous and systematic verification. Based on this observation, the authors previously reported on the interaction between an edge and an embedded parallel crack in 2-D scenarios. Since crack configurations detected using non-destructive methods in the real world are generally 3-D in nature, the study of 3-D interaction of non-aligned flaws is deemed necessary in order to obtain more practical guidance in the usage of rules speculated in Fitness-for-Service. In this study, the 3D interaction between a corner flaw and a non-aligned parallel surface flaw in an infinitely large plate is investigated to correlate better the criteria and standards from various resources in recommending the usage of those standards for the purpose of Fitness-for-Service and to classify them as either conservative or non-conservative.